Cardiac recovery following left ventricular assist device therapy: experience of complete device explantation including ventricular patch plasty. (27th December 2020) - Gyoten, Takayuki; Rojas, Sebastian V; Fox, Henrik; Hata, Masatoshi; Deutsch, Marcus-André; Schramm, René; Gummert, Jan F; Morshuis, Michiel
Abstract:  : OBJECTIVES: Myocardial recovery is a rare phenomenon in left ventricular assist device (LVAD) therapy. Surgical LVAD removal is associated with the risk of cardiac failure, and the individual evaluation of sufficient myocardial recovery is crucial. Thus, complete device explantation is not consistently performed to minimize perioperative risk. However, the remaining ventricular assist device components bear significant risks of infection or thrombosis. Therefore, we developed this study to evaluate a complete LVAD explantation protocol. METHODS: All patients in our institution who had an LVAD explanted were enrolled in the study. Explant surgery involved removal of the driveline, pump housing, sewing ring and outflow graft. The ventricular wall was reconstructed by double patch plasty. Our analysis focused on surgical and postoperative outcome parameters, including all-cause mortality and major adverse cardiac and cerebrovascular events. RESULTS: A total of 12 patients (HVAD, n  = 5; HeartMate II, n  = 3; HeartMate 3, n  = 4) had myocardial recovery and qualified for our LVAD explantation study protocol [median age: 40 years, interquartile range (IQR) 33–52 years; 50% men]. Primary heart failure aetiology: myocarditis ( n  = 5), dilated cardiomyopathy ( n  = 4), toxic cardiomyopathy ( n  = 2) and valvular heart failure ( n  = 1). The median average duration on LVAD was 10 months (25–75%: IQR 8.5–30 months). The median left ventricular ejection fraction was 15% (IQR 13–18%) at LVAD implantation and 50% (IQR 45–50%) before LVAD explantation ( P  = 0.0025).The 30-day survival was 100%. The 1-year survival was 91.7%. All patients were discharged after a median 13 days (IQR 10–18 days) postoperatively. No patient had major adverse cardiac and cerebrovascular events. The New York Heart Association functional class remained consistent during the follow-up period (median New York Heart Association functional class: II, IQR II–II class) including preservation of ventricular function. CONCLUSIONS: Complete LVAD explantation with ventricular patch plasty is feasible and has consistent long-term results.